THE OUTBREAK’S MODELING OF CORONAVIRUS (COVID-19) USING THE MODIFIED SEIR MODEL IN INDONESIA - Rustan Rustan; Linda Handayani (Program Studi Fisika Universitas Negeri Jakarta, 2020)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by a new type of virus called SARS-CoV-2, and by the beginning of 2020 had spread throughout the world, including Indonesia. A high rate of spread of COVID-19 causes the number of patients that infected increase significantly. In this study, mathematical modeling was carried out to predict the number of COVID-19 patients and the duration of the COVID-19 pandemic in Indonesia. The model used is a modified SEIR model (Susceptible, Exposed, Infected, Recovered) with several assumptions such as a constant and homogeneous population, patients who have recovered can not be infected, and the spread only occurs from human to human. In addition, it is assumed that there are individuals who carry out quarantine and isolation. Modeling is done using the help of MATLAB R2015a. The modeling results show that the peak of the COVID-19 pandemic in Indonesia will occur in the middle of May 2020, and the number of infected patients will be about 15000 people. This amount can be reduced if the quarantine and self-isolation process is carried out optimally.